Island of Guanyin: Mount Putuo and Its Gazetteers, by Marcus Bingenheimer - Crowe, Paul (Religious Studies and Theology, 2020)
Island of Guanyin: Mount Putuo and Its Gazetteers. Marcus Bingenheimer. Oxford University Press, 2016. i-xii + 283 pp. Seventeen b/w illustrations. Hb., 144. ISBN: 978-0-19-045619.